Cantor's dilemma: approximations between experimentation, literature and natural sciences teaching - Fabio Peres Gonçalves; Elisa Prestes Massena (Universidade Estadual de Maringá, 2020)
Research indicates the potential of literary works to be used in teaching natural sciences. This text deals with Carl Djerassi's Cantor's dilemma (1991), a material that portrait intrigues from the academic world in the form of fiction. The objective of the present study was to investigate the potential of this work for the approach of experimentation in training natural sciences teachers from various fields. The work was analyzed according to the procedures of the discursive textual analysis and two emergent categories were constructed: 'epistemological issues associated to experimentation' and 'the laboratory diary in scientific activity'. The analysis pointed out the potential of the work to favor the debate regarding: the function of experimentation in the refutation/confirmation of hypotheses and their social nature; the non-reduction of the work with experiments to the action in the laboratory; the association between experimentation and error; and writing in laboratory journals and related aspects.